A review on liposomal amphotericin b in antifungal therapy - A, Tirupathi Reddy; Basu , venkateshwara Reddy; A, Ganesh; D, Asiya fathema; V, Usha; M, Sai Sandhya (International Journal of Indigenous Herbs and Drugs, 2021)
To reduce the in-vivo toxicity of the broad-spectrum antifungal drug amphotericin B, various lipid formulations of amphotericin B, ranging from lipid complexes to small unilamellar liposomes, have been developed and subsequently commercialized. These structurally diverse formulations differ in their serum pharmacokinetics as well as their tissue localization, tissue retention, and toxicity. This difference can affect the choice of formulation for a given infection, the time of initiation of treatment, and the dosing regimen. Although preclinical studies have shown similarities in the in-vitro and in-vivo antifungal activity of the formulations with comparable dosing, their acute, and chronic toxicity. Profiles are not the same, and this has a significant impact on their therapeutic indices, especially in high-risk, immunosuppressed patients. With the recent introduction of new antifungal drugs to treat the increasing numbers of infected patients, the amphotericin B lipid formulations are now being studied to evaluate their potential in combinational drug regimens. With proven efficacy demonstrated during the past decade, it is expected that amphotericin B lipid formulations will remain an important part of antifungal drug therapy.